AB1413-HPR Advantages of rheumatology nursing vaccination of patients with inflammatory rheumatic diseases of autoimmune origin. analysis of the first 3 years. (12th June 2018) - Pons-Bas, A; Ivars, E.; Cano, C.; Lorente, M.; Rosas, J.; Santos-Soler, G.; Salas, E.; Senabre-Gallego, J.M.; Barber, X.; ,
Abstract : Background: Patients with systemic autoimmune diseases (SAD) have higher incidence of infections. In our Service, until 2014 about 50% of patients did not complete vaccination for pneumococcus or hepatitis B virus (HBV). Objectives: To know the characteristics of vaccinated patients and advantages of vaccination by Rheumatology nurse (Nurse-RHEU). Methods: Observational study of patients in follow-up in rheumatology, vaccinated from 2015–2017, by SAD in treatment with biological therapy and/or immunosuppressive, by Nurse-RHEU, following the recommendations from SVR and the Valencian Society of Preventive Medicine and Public Health Consensus Document for the vaccination of patients with SAD, published in 2014. Nurse-RHEU, assumed from 2015 the vaccination of all rheumatology patients with SAD. The vaccines to be administered were: pneumococcal (13 V and/or 23 V) and hepatitis B virus (HBV). Pneumococcal vaccination should be initiated with the conjugate/13 V type and at least 8 weeks later with a dose of polysaccharide/23 V vaccine. A single 23 V booster dose is recommended 5 years after the first dose. Only if patient have received a previous dose of 23 V, it is advisable to administer type 13 V, one year later. For the HBV vaccine, it is necessary previously check the immune status of the subject. If it is not immune, 3 doses will be administered (0–1–6 months). Since 2015, our Section has: refrigerator, electronic access to the Vaccinated Nominal Registry of the Valencian Community (it collects data of the patient, date, type, batch of vaccine administered), specific database (epidemiological data of the patients, future dose programming, access to electronic medical records) and Nurse-RHEU trained. Previously, the nurse details possible side effects, and how to act or contact. Results: Of the 261 patients vaccinated during 2015 to 2017, 65% were women, with mean age 53.57±15.50 years (10–81 years). The diagnosis was: rheumatoid arthritis: 48%, ankylosing spondylitis: 23%, psoriatic arthritis: 13%, systemic lupus erythematosus: 7%, uveitis: 4%, and others 5%. The reason for vaccination was: initiation treatment with a biological drug (51%), or immunosuppressive (49%). A total of 621 vaccines were administered, which were: 13-valent conjugate antineumotococcal: 259 (42%), 1 st VHB dose: 94 (15%), 2nd VHB dose: 85 (14%), 3rd VHB dose: 72 (12%), pneumococcal 23-valent polysaccharide: 111 (17%). All vaccines were registered in the Vaccinated Nominal Register of the Valencian Community. Conclusions: 1. Patients with SAD in biological treatment and/or immunosuppressant, vaccinated by Nurse-RHEU, achieve a completeness of all doses of vaccination, close to 100%. 2. In a large part of the patients, vaccination is scheduled at the beginning of the diagnosis of the disease, at the first consultation or immunosuppressive treatment, the same day of the visit to the Rheumatologist, avoiding unnecessary visits to the patient. 3. An adequate electronic registry allows immediate access to information from any point in the Valencian Community, through access to the computer program of the Health department. Acknowledgements: The study was supported with a research grant from the Association for Research in Rheumatology of Marina Baixa (AIRE-MB). Disclosure of Interest: None declared